Self Efficacy Of The Elderly After The COVID 19 Vaccine - Dodik Arso Wibowo (Journal of Applied Nursing and Health, 2022)
Background: The Covid-19 vaccine is aimed at the elderly to increase their immunity of the elderly and reduce the significant impact when exposed to Covid-19 at a young age. They are more susceptible to being exposed to the Covid-19 virus. Self-efficacy of the elderly who have received the covid-19 vaccine is better, and the elderly are more confident. Self-efficacy is a person's belief and ability to carry out a form of self-control over the functioning of the individual itself and events in the environment. The purpose of the study was to determine "Self-Efficacy of the Elderly After Covid-19 Vaccination". Methods: Descriptive research design, a population of 105 respondents and a sample of 16 respondents with a "purposive sampling" technique. The study was conducted from February 1 to March 1, 2022, in Gandu Village, Bogor District, Nganjuk Regency. Variable self-efficacy after being vaccinated against COVID-19 was carried out with an instrument in the form of a questionnaire, analyzed by percentage, and interpreted quantitatively. Results: Based on the study results, 16 respondents had self-efficacy among as many as 12 respondents (75%) and self-efficacy among as many as four respondents (25%). This is influenced by Age, education, Occupation, a clean environment, and the number of vaccines received. Conclusion: For this reason, to increase self-efficacy after being vaccinated against COVID-19, the elderly must continue to apply health protocols and maintain their immune system. Health workers are expected to provide an easy explanation for the elderly to understand before performing health services.